Errors’ analysis in a Portuguese version of the Token Test - Coutada, Sara Leite Braga (2018)
This study concerns a Portuguese version of the Token Test (TT), named Instructions Comprehension Test (ICT) that is part of the BANC (Coimbra Battery of Neuropsychological Assessment), and assesses receptive language. It carries out a quantitative and qualitative analysis of the errors made by children in this test, looking for the predominant errors, as well as specific difficulties in the comprehension of certain linguistic concepts. The ICT was applied to a sample of 295 children, of three age groups (7, 8 and 9 year-old), in which 149 are male and 146 are female. The errors made were categorized, quantified and object of a psycholinguistic analysis. The main errors found are related to some locatives, ordinal numbers and concepts of exclusion and temporal inversion, as well as to conjunctions. In this regard, there were difficulties in the interpretation of the coordinative conjunction and, when it connects two clauses with the same referent, and of the adversative conjunction but, when it introduces equality. The psycholinguistic analysis also drew attention to the role that working memory can have in this test. In sum, errors’ analysis evidenced comprehension difficulties inaccessible through the simple scoring of children’s answers as correct or incorrect.